A novel permeability perturbation testing method for delaminations in steel plates. Issue 4 (4th July 2022) - Qiu, Gongzhe; Kang, Yihua; Wang, Shenghan; Cheng, Si; Feng, Bo
ABSTRACT: Delaminations have been detected based on the principle of ultrasonic thickness measurement. However, there are blind zones in the detection of surface delamination. Besides, the high-speed detection system is complicated. A novel permeability perturbation testing (PPT) method for the inspection of delaminations in ferromagnetic materials is proposed in this paper. When DC magnetisation is applied in the thickness direction of steel plate, the delamination in the plate will distort the internal magnetic field, leading to local permeability perturbation. This perturbation is transmitted to the surface layer of steel plate in the thickness direction. Using a differential-type eddy current transducer, internal delaminations are detected by measuring relative variation of surface permeability. The variation of permeability in the near surface of steel plate with the movement of delamination and the change of magnetisation state of the steel plate are obtained through finite element simulation. The feasibility of the above method is further verified through an experiment. This new method has the advantage in high-speed detection of delamination.